Analisis Determinan yang Mempengaruhi Deviden Tunai Pada Perusahaan Farmasi Di Bursa Efek Indonesia - Reza Hanafi Lubis (CERED Indonesia Institute, 2022)
Investors buy shares and get dividends from the company because investors have invested funds in the company. The company's decision to distribute and pay dividends is one that requires careful consideration of various aspects. This study was conducted with the aim of knowing the effect of operating cash flow and net income on cash dividends in food and beverage companies listed on the Indonesia Stock Exchange 2012-2016. This study uses an associative approach. The type of data collected is quantitative data. The data source used is secondary data. The population in this study are food and beverage sub-sector companies listed on the Indonesia Stock Exchange 2012-2016. The sampling method used is purposive sampling. there are 9 companies used as samples in this study. The data analysis technique used is multiple linear analysis, hypothesis testing, namely: coefficient of determination (R2), partial test (t test) and simultaneous test (f test). The results of this study partially show that operating cash flow has no significant effect on cash dividends, while net income has a significant effect on cash dividends. Simultaneously operating cash flow and net income have a significant effect on cash dividends.